2018
DOI: 10.1097/ijg.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

Association of Postoperative Topical Prostaglandin Analog or Beta-Blocker Use and Incidence of Pseudophakic Cystoid Macular Edema

Abstract: To the best of our knowledge this is the largest study that has investigated the association between postoperative topical PGA or topical beta-blocker use and the incidence of pseudophakic CME. Postoperative use of both topical PGAs and topical beta-blockers was found to be associated with the incidence of pseudophakic CME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…Use of topical prostaglandin analogues has been implicated in increasing the risk of CMO [8,12]. A small case series of randomised patients to topical prostaglandin analogues (bimatoprost, latanoprost, and travoprost) noted 6 (12.5%) patients subsequently developed angiographic CMO, although only one had an associated loss of visual acuity [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of topical prostaglandin analogues has been implicated in increasing the risk of CMO [8,12]. A small case series of randomised patients to topical prostaglandin analogues (bimatoprost, latanoprost, and travoprost) noted 6 (12.5%) patients subsequently developed angiographic CMO, although only one had an associated loss of visual acuity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Wendel et al showed that apart from prostaglandin analogues, topical beta-blockers are also associated with the development of pseudophakic CMO. Through analysis of 508 cases and 5080 controls, they found the incidence of pseudophakic CMO to be statistically significantly associated with the current postoperative use of both topical PGAs [relative risk (RR), 1.86; 95% confidence interval (CI), 1.04-3.32] and topical betablockers (RR, 2.64; 95% CI, 1.08-6.49) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have identified preoperative prostaglandin use to be associated with increased risk of PCMO and a recent study of 508 cases and 5080 controls noted postoperative use of topical prostaglandins and beta‐blockers were both associated with increased incidence of PCMO. Interestingly, a prospective study of 70 patients with primary open angle glaucoma (POAG) and 68 healthy control eyes also reported that the risk of PCMO was greatest in the POAG group with prostaglandin analogue use (odds ratio 5.51).…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, just as the preceding evidence appears to be compelling in the indictment of prostaglandin analogues in the development of PCMO, 13,[26][27][28] in contrast, a large retrospective study including 3394 eyes with prostaglandin analogue use 12 reported no significant increase in risk of PCMO with topical prostaglandin analogues. Furthermore, Law et al 24 also observed that the use of preoperative and postoperative glaucoma medications was not associated with clinical CMO in a study of 700 eyes with glaucoma undergoing cataract surgery.…”
Section: Risk Factorsmentioning
confidence: 99%